Pemanfaatan Sosial Facebook Sebagai Media Belajar Pendidikan Agama Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa - Wulandari, Novy (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
Social network Facebook has become a trend among teens, hence can be used as an alternative medium of learning. This research aims to know the use of Facebook as a learning aids media of Islamic religious education, and to know the motivation of learning students using Facebook as a social networking medium helps the learning of Islamic religious education. This study uses a qualitative approach to the type of case studies. The use of case studies is intended to find out how the utilization of social media Facebook as an effective medium to increase motivation and student learning outcomes. The data obtained through interviews, observation and documentation. The results were analyzed using three steps: reduction, display, and verification. The results showed that instructional design of Islamic religious  education can utilize social media Facebook through the use of integrated learning strategies, by combining face-to-face learning in class and take advantage of Facebook as learning outside the classroom. Design of learning through Facebook can be done by making use of the feature Group, with steps: (1) create a Facebook for class experiments;  (2) Adding students into group; (3) Upload files; and (4) Conducting discussions.